2000
DOI: 10.4049/jimmunol.164.2.855
|View full text |Cite
|
Sign up to set email alerts
|

Involvement ofmi-Transcription Factor in Expression of α-Melanocyte-Stimulating Hormone Receptor in Cultured Mast Cells of Mice

Abstract: The microphthalmia (mi) locus encodes a member of the basic-helix-loop-helix-leucine zipper (bHLH-Zip) protein family of transcription factors (MITF). We have reported that expression of several genes was impaired in cultured mast cells (CMCs) of mi/mi mice due to a defective transactivation ability of mutant MITF (mi-MITF). We also found that mi/mi CMCs did not express a receptor (MC1R) for α-melanocyte-stimulating hormone. The overexpression of the wild-type (+/+) MITF but not mi-MITF normalized the expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 40 publications
2
46
0
Order By: Relevance
“…Consistent with previous work showing that Mitf activates and binds to a promoter region containing a potential Mitf binding site (58,59), Mitf was also associated with the endogenous Mc-1r promoter, and activation of the Mc-1r gene correlated with hyperacetylation of histone H4. Thus, Mitf may recruit histone acetyltransferases but not SWI/SNF enzymes to the Mc-1r promoter.…”
Section: Mitf Promotes Recruitment Of Swi/snf Enzymes To and Histone supporting
confidence: 77%
See 1 more Smart Citation
“…Consistent with previous work showing that Mitf activates and binds to a promoter region containing a potential Mitf binding site (58,59), Mitf was also associated with the endogenous Mc-1r promoter, and activation of the Mc-1r gene correlated with hyperacetylation of histone H4. Thus, Mitf may recruit histone acetyltransferases but not SWI/SNF enzymes to the Mc-1r promoter.…”
Section: Mitf Promotes Recruitment Of Swi/snf Enzymes To and Histone supporting
confidence: 77%
“…It binds to the melanocortin-1 receptor (Mc-1r), a member of a subfamily of G protein-coupled receptors that is expressed in melanocytes and other cells (82). Mitf has been shown to activate the Mc-1r promoter in both melanocytes and mast cells (58,59); therefore, we tested whether Mitf could activate Mc-1r expression in fibroblasts and whether its expression required SWI/SNF enzymes. We found that Mc-1r was expressed in fibroblasts at low levels and was activated by Mitf in an SWI/SNF-independent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Pigmentation-associated transcriptional targets of MITF include the pigment enzyme genes tyrosinase, TRP1, TRP2/Dct, which were recognized to contain an evolutionarily conserved consensus promoter/enhancer element that matches the MITF recognition sequence (Bentley et al 1994;Hemesath et al 1994;Yasumoto et al 1994). Additional differentiation-associated genes include Pmel17/silver/gp100 (which encodes the melanoma diagnostic epitope HMB45) (Halaban et al 1996;Baxter and Pavan 2003;Du et al 2003), MelanA/Mart1 , Melastatin (TRPM1) (Miller et al 2004;Zhiqi et al 2004), AIM1 (ocular albinism 4 gene) (Du and Fisher 2002), Ocular albinism 1 gene (OA1) (Vetrini et al 2004), VMD2 (Esumi et al 2004), HIF1␣ (Busca et al 2005), Plasminogen activator inhibitor-1 (Murakami et al 2006), numerous mast cell targets of MITF including Prostaglandin D2, multiple mast cell genes including proteases, various adhesion molecules and others (see Ito et al 2004;Morii et al 2004;Takeda et al 2006 and references therein), and melanocortin 1 receptor (MC1R) in mast cells and possibly in melanocytes (Adachi et al 2000;Smith et al 2001;Aoki and Moro 2002). Numerous additional genes are being identified through expression microarrays, and are liable to reflect the multiple steps involved between signaling, expressing, packaging, and exporting pigment.…”
Section: Transcriptional Targets Of Mitfmentioning
confidence: 99%
“…21 E-box is present immediately upstream of the transcriptional initiation site. 28,29) The presence of an E-box suggests the possibility that MITF regulates Mc1r gene expression by the same transcriptional mechanism as Tyr and Trp1. 28) Thus MITF appears to play a central role in the expression of the enzymes and receptors essential to melanogenesis.…”
Section: Discussionmentioning
confidence: 99%